THE FUTURE OF EURASIAN LOGISTICS: EXPANDING TRANSPORT NETWORKS ACROSS CENTRAL ASIA (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In recent decades, Central Asia has emerged as a pivotal region in the transformation of Eurasian logistics. Geopolitical shifts, increased infrastructure investment, evolving global trade flows, and sanctions have accelerated the creation of new transport corridors, including the so-called Middle Corridor. This article examines the key trends shaping Eurasian logistics and outlines Central Asia’s prospects as an integrated logistics hub.